Application of quadratic regression orthogonal design to develop a composite inoculum for promoting lignocellulose degradation during green waste composting. (September 2018) - Yu, Kefei; Sun, Xiangyang; Li, Suyan; Cai, Linlin; Zhang, Pengfei; Kang, Yue; Yu, Zhihao; Tong, Jing; Wang, Lin
Highlights: Three lignocellulolytic microorganisms were isolated from compost of green waste. Quadratic regression orthogonal design is feasible to develop composite inocula. The composite inoculum has a considerable effect of lignocellulose degradation. Abstract: The aims of this study are to determine the feasibility of applying QROD (quadratic regression orthogonal design) to optimize a combination of microorganisms and to develop a composite inoculum for promoting lignocellulose degradation during GWC (green waste composting). This feasibility was studied in a laboratory scale experiment, using three lignocellulolytic microorganisms, isolated from the mature phase of GWC by the dilution plating method. After the feasibility was confirmed, a composite inoculum was developed through the results of the optimization, whose effect was evaluated by comparing it with Phanerochaete chrysosporium and EM (Effective Microorganisms) in a pilot scale experiment of GWC. The use of QROD to finish this optimization was proven feasible, because the p value of the regression equation was less than 0.05 (0.0108), meaning that the quadratic regression model is suitable for describing the relationship between the combination of the three microorganisms and their ability to degrade lignocellulose. Additional proof of this feasibility is that the composite inoculum in the quadratic regression orthogonal experiment demonstrated lignocellulose degradation ability similar to the GWC experiment. Although the lignin degradation ability of the composite inoculum did not surpass Phanerochaete chrysosporium, it was stronger than EM. Meanwhile, cellulose degradation ability and humus synthesis ability of the composite inoculum were stronger than for Phanerochaete chrysosporium and were close to EM. It is hard to tell which inoculum is the best since each inoculum had advantages in different aspects, while the composite inoculum still showed a considerable effect of lignocellulose degradation during GWC.